Unveiling Causal Complexity in Mathematics Achievement: A Research Design using Fuzzy-Set Qualitative Comparative Analysis (FS/QCA) - Filiestianto, Gerry (Universitas Muhammadiyah Surakarta, 2025)
Mathematics achievement is a critical indicator of educational success and a key determinant for future STEM careers. However, national assessments in Indonesia reveal persistent challenges and significant learning gaps in student numeracy. Existing research has identified a multitude of influencing factors, yet predominantly relies on linear models (e.g., regression, SEM) that estimate the 'net effect' of each variable in isolation. This approach overlooks the complex causal configurations where different factors interact synergistically. This paper addresses this methodological gap by proposing a research design that employs fuzzy-set Qualitative Comparative Analysis (fs/QCA). The study will utilize secondary data from the Indonesian National Assessment to analyze how combinations of school, family, and student-level conditions lead to high mathematics achievement. The expected contribution is the identification of multiple, distinct pathways-or 'causal recipes'-to success, offering a more nuanced foundation for developing targeted and context-specific educational policies.